From Photon to Neuron: Light, Imaging, Vision - Jafri , Mishkat Ali; Ulfat, Intikhab (International Journal of Endorsing Health Science Research, 2024)
We present a book review of "From Photon to Neuron: Light, Imaging, Vision" by Philip Nelson. The book offers a remarkable journey at the intersection of physics and biology, authored by a distinguished professor of physics at the University of Pennsylvania. With a focus on fundamental concepts of light, imaging, and vision, the book caters to a diverse audience, from undergraduates to advanced researchers. Organized into three parts, it explores topics such as direct image formation, visual perception mechanisms, and advanced quantum behaviors of electrons and photons. While the book excels in its interdisciplinary approach and practical learning emphasis, potential areas for improvement include enhancing accessibility for readers without a background in quantum physics and adapting content to diverse audiences. "From Photon to Neuron" stands as a pioneering masterpiece that educates and empowers students with essential skills for navigating the complex realms of physics and biology.